The knee alignment and the foot arch in patients with Turner syndrome Ukształtowanie kolan i wysklepienie stóp u chorych z zespołem Turnera - Katarzyna Milde; Andrzej Wiśniewski; Elżbieta Olszewska; Dorota Trzcińska; Marcin Madej (Pediatric Endocrinology, Diabetes and Metabolism)
Introduction: It is established that patients with Turner syndrome (TS) have numerous defects of the skeletal system, including in the lower extremities structure. However, there are not enough studies in the literature about knee alignment and foot arches in girls and women with TS. Aim of the study: Assessment of knees and feet in girls and women with TS. Material and methods: Sixty-two girls and women with TS were examined. The mean chronological age of the patients was 15.61±5.27 years, ranging from 6.36 to 27.04-years-old. All patients underwent physical examinations of their knees and feet. Additionally, almost 70% (n=42) underwent plantographic examinations and measurement of their heel angle and Clarke’s angle. The formation of the foot in patients with TS was related to the reference values developed on the basis of studies of healthy girls (n=92). In women whose knee conditions were assessed only on the basis of a physical examination, a drawer test was performed each time to assess the stability of the knee ligament systems. Results: In over 60% of patients with TS, incorrect knee alignment, primarily in the form of genu valgum (knock-knee), was diagnosed. At the same time, 60% of the patients tested only in physical examinations were diagnosed with knee ligament instabilities (positive drawer test). Physical examinations showing foot arch malformation – in equal proportion splay-foot and low-arched – were found in almost two-thirds of women with TS. However, on the basis of plantography, abnormalities in the longitudinal arch of the foot were diagnosed in 60% of patients with TS, and abnormalities in the transverse arch of the foot were diagnosed in 80% of patients with TS. Conclusions: In patients with TS, the occurrence of the following is characteristic: 1. Genu valgum of knees and heels; 2. Frequent cases of abnormally formed longitudinal and transverse arches of the foot, with the longitudinal arch of the foot usually being reduced, while the transverse arch is excessively elevated; 3. Asymmetry involving a frequent occurrence of different types of abnormalities in the arches of the left and right foot, and the possible occurrence of normal knee alignment with an abnormal formation of the feet, or incorrect knee alignment with normal formation of the arches in both feet. The presence of the aforementioned disorders of knee alignment and foot arches authorizes us to recommend a routine assessment of posture, knee alignment, and the arch of the foot in all patients with Turner syndrome and, if irregularities are found, to direct patients for corrective treatment of the musculoskeletal system disorders.